Adaptation as an Integrated System of Clinical-Anamnestic, Immunological and Psychological Components in Children Raised in Orphanages - I.L. Vysochynа (Zaslavsky O.Yu., 2013)
The aim of the study was to investigate the characteristics of adaptation of orphanages on the basis of the findings of a comprehensive study of the components of this phenomenon and develop a mathematical model of evaluation of the current state of adaptation using correlation analysis. The study included 361 children from orphanages in age from 3 to 17 years in a state of clinical well-being. The correlation analysis of 512 indicators that were studied (the multiplicity of SARS in history, the presence of chronic foci of infection, the results of dispensary examination of children, evaluation of physical development, the characteristics of ecological community mucous TTP, the presence of clinical symptoms of post-infectious fatigue, data on medical history and the results of immunological examination - content leukocytes, lymphocytes, CD25+, serum immunoglobulins A, F, G, cytokines (IL-2, IL-4, IL-10; IL-12р70+, IL-12p40+p70+; TFGβ1) in peripheral blood and the concentration of antimicrobial proteins (alpha-defensins 1-3, lactoferrin) and SIgA in oropharyngeal secretions, psychological pattern-typological characteristics (test Eysenck, Shmishek, tapping test), assessment of the color of associative reactions (Lüscher test, the test color relations), features a portrait of emotional (anxiety, SAN), and identification donozologichnih neurotic border states). Statistical processing has identified the most important factors for a data set of results which can determine the level of adaptation of orphanages.